2011
DOI: 10.1089/jpm.2010.0363
|View full text |Cite
|
Sign up to set email alerts
|

The Use of High Dose Rate Brachytherapy Palliation after Failed Palliative External Beam Radiotherapy for a Cutaneous Malignant Melanoma of the Foot: A Case Report

Abstract: High dose rate brachytherapy may have a substantial impact on the management of cutaneous lesions, but further studies on its efficacy and toxicity must be evaluated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…A randomized trial showed that there was eye preservation but no worse survival with BT versus enucleation . BT can also be used to treat cutaneous and mucosal melanomas. In a phase one trial of hyperthermia with low dose rate BT the control rate in a small number of patients with cutaneous melanoma metastases was excellent.…”
Section: Modalities Of Radiation Therapymentioning
confidence: 99%
“…A randomized trial showed that there was eye preservation but no worse survival with BT versus enucleation . BT can also be used to treat cutaneous and mucosal melanomas. In a phase one trial of hyperthermia with low dose rate BT the control rate in a small number of patients with cutaneous melanoma metastases was excellent.…”
Section: Modalities Of Radiation Therapymentioning
confidence: 99%